Characterization of CD3γ/δ gene and its immune response in Qihe crucian carp Carassius auratus after challenged by Aeromonas veronii and Poly(I:C). Issue 133 (February 2023) - Tang, Hairong; Zhu, Lei; Zhao, Xianliang; Jiang, Xinyu; Zhang, Jie; Pei, Chao; Li, Li; Kong, Xianghui
Abstract: CD3γ/δ found in non-mammalian vertebrates is a CD3 homolog with structural characteristics similar to both mammalian CD3γ and CD3δ, and plays important roles in T cell recognization and immune response in fish. In this study, the full-length of CD3γ/δ from Qihe crucian carp (named CaCD3γ/δ ) was cloned and characterized, then the expression response profiles and potential immune functions was explored after Aeromonas veronii and Poly(I:C) challenge. The results showed that the full-length of CaCD3γ/δ was 819 bp including a 5ʹ-UTR of 141 bp, a 3ʹ-UTR of 168 bp, and an ORF of 510 bp encoding a putative 169-aa protein with an estimated MW of 18.71 kD and a theoretical pI of 8.77. The protein sequence of CaCD3γ/δ contained a Leu-Leu and a CXXXC motif in the extracellular domain, and an ITAM and a Leu-Ile motif in the cytoplasm, and a residue of Asn in the transmembrane. CaCD3γ/δ was constitutively expressed in the spleen, liver, gill, and blood of Qihe crucian carp. After the carp were challenged with Poly(I:C) and Aeromonas veronii, the mRNA expression levels of CaCD3γ/δ were significantly changed in the spleen, head kidney, intestine and gill, according to the results of qPCR. However, compared with A. veronii, Poly(I:C) challenge can rapidly induce the CaCD3γ/δ expression levels in head kidney, intestine and spleen, which suggested CaCD3γ/δ may be differentially modulated by different pathogens. Moreover, the results of immunohistochemical analysis showed that the CaCD3γ/δ + secreted cells in the spleen and gills of Qihe crucian were increased after challenged with Poly(I:C), as well as the spleen challenged with A. veronii, but at different levels. Combined with the fact that vascular congestion, necrosis of parenchymal cells, and inflammatory cells including lymphocytes infiltration were also observed in the gill and spleen of Qihe crucian carp treated with A. veronii and Poly(I:C) revealed by pathological analysis, it was predicted that Ca CD3γ/δ + T lymphocytes may participated in the immune response against pathogens. This study will contribute to understand the important role of Ca CD3γ/δ + T lymphocytes in the immune response of Qihe crucian carp, and provide new insights for the prevention and treatment of the diseases of Qihe crucian carp. Highlights: The full-length of CD3γ/δ from Qihe crucian carp (named CaCD3γ/δ ) was obtained. The CaCD3γ/δ was significantly changed after challenged with Poly(I:C) and Aeromonas veronii. The CaCD3γ/δ + secreted cells were increased after challenged with Poly(I:C) and A. veronii. Poly(I:C) and A. veronii could cause serious tissues damage in the immune organs.